Disrupted Stratospheric QBO Signatures in the Diurnal Tides Over the Low‐Latitude MLT Region. Issue 10 (19th May 2021) - Pramitha, M.; Kishore Kumar, K.; Venkat Ratnam, M.; Praveen, M.; Rao, S. Vijaya Bhaskara
Abstract: Meteor radar measurements of winds in the mesosphere and lower thermosphere (MLT) over Tirupati (13.63°N, 79.4°E; 2013–2020) and Microwave Limb Sounder (MLS) observations of ozone are used for investigating the effect of the disrupted stratospheric quasi‐biennial oscillation (SQBO) during the year 2016 on the diurnal tides. The positive tidal perturbations are observed during positive perturbations of ozone and eastward phase of the SQBO and vice versa. These observations are well captured by the Specified Dynamics Whole Atmosphere Community Climate Model (SD‐WACCM) simulations. The results suggest that the ozone and wind perturbations in the stratosphere induced by the sudden phase transition in the SQBO winds are the potential candidates for the observed abrupt changes in the diurnal tide amplitudes in the MLT region. The SQBO disruption thus provided an opportunity to seek further insights into the pathways through which the lower atmosphere influence the middle and upper atmosphere. Plain Language Summary: Atmospheric tides are global scale oscillations with periods that are sub‐harmonics of a solar day (24, 12, 8 h etc.). Among these, diurnal tides (24 h) are very prominent over low latitudes and play a major role in shaping the structure and dynamics of the middle atmosphere. Stratospheric quasi‐biennial oscillation (SQBO) is a long period oscillation with a mean time period of ∼28 months in the stratosphere and is believed to modulate diurnal tides at interannual time scales. During the year 2016, for the first time the SQBO disruption took place. The present study investigates the effect of the SQBO disruption on the amplitudes of the diurnal tides in the MLT region using meteor radar observations over a low‐latitude station. Stratospheric ozone measurements obtained from Microwave Limb Sounder (MLS) as well as simulations from Specified Dynamics Whole Atmosphere Community Climate Model (SD‐WACCM) are also employed to shed light on the relation among diurnal tides, SQBO winds and ozone. The results suggest a positive correlation between diurnal tide perturbations and ozone perturbations as well as SQBO winds. During the SQBO disruption, there is a negative anomaly in the ozone perturbations and westward winds below 20 hPa, which are thought to be the prime candidates in reducing the observed diurnal tide amplitudes in the MLT. Key Points: Response of diurnal tides in the low‐latitude mesosphere and lower thermosphere region to the stratospheric quasi‐biennial oscillation (SQBO) disruption during the year 2016 is investigated Observed reduction in the diurnal tide amplitudes is associated with the stratospheric winds as well as ozone variability at SQBO scales Quasi‐biennial oscillation disruption though lasted for a brief period, its effect is noted for a relatively longer period